Students' Socio-Cultural Competence Formation in Project Activity (Examplified by the Foreign Language Teaching) - N. G. Murayeva (Russian State Vocational Pedagogical University, 2015)
The paper deals with the model fostering the socio-cultural competence of the higher school students. The model in question is based on the integration of project activities and Web 2.0 information technologies, the methods facilitating its implementation being described along with the teaching means and forms, and socio-cultural competence formation levels. The author demonstrates the complex of problematic tasks which become more complicated depending on the acquired level of the above competence, and mastered skills and abilities. The tree types of socio-cultural projects are recommended according to the achieved levels: mini-project, web quest and web project. The suggested model fulfills the idea of pedagogic facilitation of the foreign language learning by using the meaning formation mechanism in socio- cultural educational environment. The author argues that its introduction into the higher school training process can promote the students' interest to the different culture and mentality, and their readiness for the cross-cultural dialog over the internet.